An assessment of the effect of Na2SiO3/NaOH ratio, NaOH solution concentration, and aging on the fracture properties of ultra-high-performance geopolymer concrete: The application of the work of fracture and size effect methods. (May 2022) - Ghasemzadeh Mousavinejad, Seyed Hosein; Sammak, Moein
Highlights: UHPGC fracture characteristics were calculated based on the work-of-fracture method and size effect method. As the Na2SiO3/NaOH ratio and molarity increase, the fracture energy increases and the ductility decreases. With increasing age, the fracture energy and brittleness increase. The specimens could obtain over 90% of the total fracture energy of the 28-day age at early ages. Abstract: This experimental study deals with the effects of Na2 SiO3 to NaOH solution ratio (SS/SH) (at three levels of 1, 2, and 3), NaOH solution concentration (at three levels of 8, 12, and 16 M), and aging (at three levels of 3, 7 and 28 days) on the fracture characteristics of ultra-high-performance geopolymer concrete (UHPGC) based on ground granulated blast furnace slag (GGBFS) and silica fume. So, five mix proportions were selected. Fracture parameters, including total fracture energy (GF ), initial fracture energy (Gf ), characteristic length (Lch ), the effective size of process zone (Cf ), brittleness number (β), fracture toughness (KIC ), and critical effective crack- tip-opening displacement (δc ), were calculated based on the work-of-fracture (WF) method and size effect (SE) method, and a comparison was made among the results. So, sixty notched beams were subjected to the three-point bending test. The results showed that with increasing SS/SH ratio, molarity, and aging, fracture energy increased and ductility decreased. The specimens up to the age of 7 days could obtain over 90% of the total fracture energy obtained at the age of 28 days. Furthermore, fracture energy increased with the improvement of mechanical properties. The specimen with an SS/HS ratio of 3 and morality of 16 exhibited the highest fracture energy and the lowest ductility. Finally, GF /Gf ratio was calculated as an important parameter in fracture mechanics, which decreased with increasing total fracture energy and initial fracture energy. The mix proportion with the highest fracture energy had the lowest GF /Gf ratio.